Multiple quantitative trait loci contribute to resistance to bacterial canker incited by Pseudomonas syringae pv. actinidiae in kiwifruit (Actinidia chinensis). Issue 1 (1st September 2019) - Tahir, Jibran; Hoyte, Stephen; Bassett, Heather; Brendolise, Cyril; Chatterjee, Abhishek; Templeton, Kerry; Deng, Cecilia; Crowhurst, Ross; Montefiori, Mirco; Morgan, Ed; Wotton, Andrew; Funnell, Keith; et al.
Abstract: Pseudomonas syringae pv. actinidiae (Psa) biovar 3, a virulent, canker-inducing pathogen is an economic threat to the kiwifruit ( Actinidia spp.) industry worldwide. The commercially grown diploid (2×) A. chinensis var. chinensis is more susceptible to Psa than tetraploid and hexaploid kiwifruit. However information on the genetic loci modulating Psa resistance in kiwifruit is not available. Here we report mapping of quantitative trait loci (QTLs) regulating resistance to Psa in a diploid kiwifruit population, derived from a cross between an elite Psa-susceptible 'Hort16A' and a resistant male breeding parent P1. Using high-density genetic maps and intensive phenotyping, we identified a single QTL for Psa resistance on Linkage Group (LG) 27 of 'Hort16A' revealing 16–19% phenotypic variance and candidate alleles for susceptibility and resistance at this loci. In addition, six minor QTLs were identified in P1 on distinct LGs, exerting 4–9% variance. Resistance in the F1 population is improved by additive effects from 'Hort16A' and P1 QTLs providing evidence that divergent genetic pathways interact to combat the virulent Psa strain. Two different bioassays further identified new QTLs for tissue-specific responses to Psa. The genetic marker at LG27 QTL was further verified for association with Psa resistance in diploid Actinidia chinensis populations. Transcriptome analysis of Psa-resistant and susceptible genotypes in field revealed hallmarks of basal defense and provided candidate RNA-biomarkers for screening for Psa resistance in greenhouse conditions.